Hubungan Intimate Friendship Dan Motif Diversi Dengan Pengungkapan Diri Pada Mahasiswa Pengguna Instagram - Syafitri, Nyimas Nabila; Islamia, Intan; Syafrimen, Syafrimen (ANFUSINA: Journal of Psychology, 2021)
Self-disclosure is an activity to convey information about oneself to others who are considered close and need at least one other person. One of the factors that influence self is intimate friendship and diversity of motives. This study aims to determine the relationship of friendship and diversion motives with self in students using Instagram. The hypothesis in this study is the relationship between intimate friendship and diversion motives with self in students. The population in this study were students of the Islamic Psychology Study Program, UIN Raden Intan Lampung. The sampling technique used is purposive sampling. The sample in this study amounted to 90 respondents.The measuring instrument used is the self scale, intimate friendship scale and motive diversion scale. The analysis technique used is multiple regression with the help of JASP software ver 0.16.0.0 for windows. The results of the study can be seen from the value of R = 0.514 and the value of F = 15.585 with a significance of p < 0.001 and an effective contribution of 26.4%, which means that there is a significant relationship between intimate friendships and self-diversion motives for students using Instagram. Then the value (rx1-y) -0.344 and p <0.001, the effective contribution is 13.20%, so there is a negative and significant relationship between intimate friendships with oneself in students with. The value (rx2-y) is 0.343 and p < 0.01, a contribution of 13.13%, so there is a positive and significant relationship between the diversion motive and self-effectiveness in students. Keywords: Intimate friendship, Diversion Motive, Self Disclosure